2020
DOI: 10.2217/pgs-2019-0146
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibilities and Prediction Modeling of Carbamazepine and Allopurinol-Induced Severe Cutaneous Adverse Reactions in Vietnamese

Abstract: Aims: To determine genetic susceptibility markers for carbamazepine (CBZ) and allopurinol-induced severe cutaneous adverse reactions (SCARs) in Vietnamese. Methods: A case–control study was performed involving 122 patients with CBZ or allopurinol-induced SCARs and 120 drug tolerant controls. Results: HLA-B*58:01 was strongly associated with allopurinol-induced SCARs and strongly correlated with SNP rs9263726. HLA-B*15:02 was associated with CBZ-induced Stevens–Johnson syndrome/toxic epidermal necrolysis but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In 2018, the allopurinol drug label was updated to include pharmacogenetic guidance, however, despite the evidence supporting the association, replication across different races/ancestries, and guidance from medical societies, testing is recommended rather than required. Since this update, studies have also confirmed the HLA‐B*58:01‐ allopurinol association in Vietnamese, 72 Brazilian, 73 and Malaysian patients 74 . Notably, the 2020 ACR gout treatment guideline update added an additional recommendation for HLA‐B*58:01 screening in African Americans 75 …”
Section: Human Leukocyte Antigen: the Untapped Hotspot For Pharmacogenomic Actionability?mentioning
confidence: 89%
“…In 2018, the allopurinol drug label was updated to include pharmacogenetic guidance, however, despite the evidence supporting the association, replication across different races/ancestries, and guidance from medical societies, testing is recommended rather than required. Since this update, studies have also confirmed the HLA‐B*58:01‐ allopurinol association in Vietnamese, 72 Brazilian, 73 and Malaysian patients 74 . Notably, the 2020 ACR gout treatment guideline update added an additional recommendation for HLA‐B*58:01 screening in African Americans 75 …”
Section: Human Leukocyte Antigen: the Untapped Hotspot For Pharmacogenomic Actionability?mentioning
confidence: 89%
“…Both allopurinol and lenalidomide were possible causes for DRESS in patient 9. Allopurinol is one of the leading causes of DRESS globally [ 25 ] with few cases associated with lenalidomide to date [ 26 ]. Surprisingly, the patient had a positive XTT–LTT to lenalidomide and not allopurinol or its metabolite oxypurinol [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both allopurinol and lenalidomide were possible causes for DRESS in patient 9. Allopurinol is one of the leading causes of DRESS globally (25) with few cases associated with lenalidomide to date(26). Surprisingly, the patient had a positive XTT-LTT to lenalidomide and not allopurinol or its metabolite oxypurinol (27).…”
Section: Discussionmentioning
confidence: 99%